Subsídio para gestão das águas subterrâneas na bacia hidrográfica do rio Santa Maria/RS - Descovi Filho, Leonidas Luiz Volcato (2009)
This study aims to provide subsidies for groundwater management at the basin of Rio Santa Maria-BHRSM. Located in the southwest of Rio Grande do Sul state, Brazil, on the edge of Paraná Basin and transitioning towards the Uruguaio Sul-Riograndense Shield, has an area of 15,797,300 square kilometers. About 16 formations occur in outcrops Pavão (2004), of which 36% arises as the Guarani Aquifer System/GAS. The outcrop areas represent areas of direct recharge of GAS and of locally discharge on BHRSM. Four Hydrogeologic Domains have gathered CPRM (2007). Domains 1 and 2 form intergranular porous aquifers in 83.08%. Domains 5 and 6 form fissural aquifers in 16.92%. An outline for the use of draft coverage criteria was elaborated, for granting the use of groundwater: Global, Regional and Local. On the Global scale, were approached four Hydrogeologic Domains, three Hydrogeologic Provinces, seven Hydrogeologic Sub-Provinces; seven Hydrogeologic Systems (six aquifers and one aquitard) and sixteen Hydrostratigraphic Units. The Regional scale approaches the Catchment and its 21 Reference Hydrological Sections, designed for sectorizing the surface water studies and sometimes used for the management of groundwater. A database on 590 hydrogeological captures was developed. The potentiometric quotas indicating groundwater flow, vadose zone, concentrations of Total Dissolved Solids-TDS, nitrates concentrations and vulnerable to contamination of aquifers Method GOD Foster et al. (2006) were spacialized as thematic maps. The gathered information gave rise to the SIG-BHRSM shapefiles containing the plans relating to information for each theme. The preponderant use of groundwater supplies is human, by forming a greater amount of information in urban areas and gaps in rural areas. The predominant groundwater flow is south-to-north, along the trim of the natural terrain. As to the potentiometry, were acknowledged evidences of contribution of groundwater to the Rivers base flow, establishing a cross-border Brazil-Uruguay flow and vice versa. The prevalent vulnerability classes were: high 35.6%, moderate 30.2%, low 26.5%, negligible 5.7% and extreme 0.4%. The areas with information gaps accounted 1.1% of BHRSM. The overlap of the TDS test concentrations in classes 1 and 2 to the vulnerability to contamination of groundwater will apply as guideline for the implementation of management tools, integrated with other policies to protect the physical environment. These guidelines have been spatialized into three scales: the Global scale accounting 1: 250,000 or less (in general), the Regional scale rating between. 1: 250,000 and 1: 50,000 (semi-detailed), and the Local rating 1: 50,000 or higher (greater detail). This segmentation in scales intends to subsidize the implementation of integrated management tools for groundwater resources in a basin.